Effect of Local Government Size, Own-Source Revenue and Effectiveness Ratio on Financial Performance - Rifqi Dzaky Mufadhal; Afni Sirait (DINASTI RESEARCH, 2026)
The implementation of regional autonomy encourages local governments to independently manage financial resources as part of fiscal decentralization and good governance practices. Through this authority, local governments are expected to improve accountability, transparency, and efficiency in regional financial management to support public services and regional development. However, differences in fiscal capacity, local revenue generation, and effectiveness in achieving revenue targets create disparities in local government financial performance. This study aims to examine the influence of local government size, own-source revenue, and effectiveness ratio on local government financial performance. Using a quantitative approach, this research analyzes secondary data from the financial statements of regencies and cities in the Special Region of Yogyakarta and East Java during 2019–2024. Multiple linear regression analysis was employed after conducting classical assumption tests. The results indicate that local government size and own-source revenue have a positive and significant effect on financial performance, while the effectiveness ratio does not significantly affect financial performance. These findings imply that institutional capacity and fiscal independence are more influential in improving financial performance than merely achieving revenue targets. This study contributes to the development of stewardship theory in the public sector by emphasizing the importance of institutional resource management and fiscal independence in strengthening local government financial performance within the framework of regional autonomy.